Long‐term outcomes of cochlear implantation in patients with high‐frequency hearing loss. (13th January 2018) - Roland, J. Thomas; Gantz, Bruce J.; Waltzman, Susan B.; Parkinson, Aaron J.
Abstract : Objective: To demonstrate the long‐term benefits of implantation in patients with high‐frequency sensorineural hearing loss, this report provides 5‐year follow‐up on a group of implant recipients who were subjects of the Cochlear™ Nucleus ® Hybrid™ L24 Implant System pivotal clinical study. Methods: The results of three related clinical studies were compiled to provide outcome data after 1, 3, and 5 years of implant use in a group of subjects who presented with preoperative high‐frequency hearing loss and were implanted with a Nucleus Hybrid L24 (Cochlear Ltd., Sydney, Australia) cochlear implant. A subset of the 50 adult subjects (N = 32) who participated in the Hybrid L24 pivotal Investigational Device Exemption (IDE) completed comprehensive evaluations at 12 months postactivation, 3 years postactivation, and then as part of a postapproval study at 5 years postactivation. Testing included audiometric, speech perception, and subjective satisfaction measures. Results: Mean unilateral speech perception performance was significantly improved at all postoperative intervals compared to preoperative best‐aided results and has remained stable to 5 years postactivation. Ninety‐four percent of subjects had measurable hearing, and 72% continued to use electric‐acoustic stimulation in the implanted ear after 5 years of implant use. Subjective satisfaction results support objective performance improvements. Conclusion: Results demonstrate long‐term success of patients with high‐frequency hearing loss following Hybrid L24 (Cochlear) cochlear implantation. Benefits include speech perception abilities significantly better than those in the preoperative best‐aided condition, with additional benefit in those using electric‐acoustic stimulation in the implanted ear. Level of Evidence: 2b. Laryngoscope, 1939–1945, 2018